Epidemiology and genetic characterization of tet(X4)-positive Klebsiella pneumoniae and Klebsiella quasipneumoniae isolated from raw meat in Chengdu City, China - Weishuai Zhai; Yiqing Wang; Honghu Sun; Bo Fu; Qidi Zhang; Congming Wu; Jianzhong Shen; Dejun Liu; Yang Wang (Elsevier, 2024)
The rapid spread of mobile tigecycline resistance presents a significant public health threat, particularly with the increasing prevalence of tet(X4)-positive Enterobacterales across various species. This study aimed to investigate the epidemic features and transmission dynamics of tet(X4)-positive Klebsiella pneumoniae (K. pneumoniae) through the analysis of 206 raw meats, including pork (n = 182), beef (n = 16), duck (n = 5), and chicken (n = 3). These samples were collected from schools, markets, and restaurants in Chengdu City, China. A total of 25 isolates were obtained from 13 administrative regions. All isolates exhibited resistance to tetracycline, tigecycline, ampicillin, chloramphenicol, and florfenicol. Over half of the isolates also demonstrated resistance to streptomycin (80 %), sulfamethoxazole/trimethoprim (72 %), ciprofloxacin (64 %), and ampicillin/sulbactam (56 %). Among these strains, 14 distinct sequence types (STs) were identified, revealing evidence of inter-regional clonal spread, notably among 9 K. pneumoniae ST3393. Phylogenetic analysis revealed the presence of two K. pneumoniae ST5 closely resembling hypervirulent K. pneumoniae from Jiangsu. Importantly, 12 isolates were capable of transferring tigecycline resistance to Escherichia coli J53. Further plasmid analysis showed that the tet(X4)-harboring plasmids in K. pneumoniae could be classified into four types, primarily belonging to the IncFIA(HI1)/HI1A/HI1B hybrid plasmid (n = 16) and IncFII plasmid (n = 7), which significantly contributed to the cross-species dissemination of tet(X4). In summary, this study highlights the prevalence of MDR tet(X4)-positive K. pneumoniae in Chengdu, driven predominantly by clonal expansion and plasmid-mediated horizontal gene transfer. These findings emphasize the importance of continuous surveillance of tet(X4)-positive K. pneumoniae in raw meat and the implementation of effective measures to control their spread.